-48+x=23

Simple and best practice solution for -48+x=23 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -48+x=23 equation:


Simplifying
-48 + x = 23

Solving
-48 + x = 23

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '48' to each side of the equation.
-48 + 48 + x = 23 + 48

Combine like terms: -48 + 48 = 0
0 + x = 23 + 48
x = 23 + 48

Combine like terms: 23 + 48 = 71
x = 71

Simplifying
x = 71

See similar equations:

| (X-2)+7X=-26 | | 9(h-2)=18 | | -9(x+7)-6=-69 | | x+-47=86 | | 4x+-28=-28+6x | | 4x+11=-3 | | p^2=305 | | 3ab^2+5a^2b-a=2b | | x-(-2)=23 | | 2+7z= | | 5x-180=11x+76 | | 6n-46=3n-7 | | x^3-2ix^2-5x=0 | | 6x*6=-6 | | y-(-4)=5(x-3) | | -19+x=14 | | 17.8x+5[6-(2x+3)]= | | P^2+2p-24= | | -(1-(-2)2)2-5x(-2)= | | 324=2X+(X-84) | | 24+7x=9x+14 | | x-(-11)=17 | | y+4x-2=0 | | -6x-10=19-5x | | 13+x=-20 | | 3*4.5-y=9 | | 2x^2+3y^2+12x-12y-210=0 | | 7(2x+9)=3x+100 | | 6+3*5-2=18 | | 5(3x-6)=12 | | 19=23-2v | | -2(4x-2)+6x=4(x+3) |

Equations solver categories